Acute effects of calcium supplements on blood pressure and blood coagulation: secondary analysis of a randomised controlled trial in post-menopausal women. Issue 11 (30th September 2015) - Bristow, Sarah M.; Gamble, Greg D.; Stewart, Angela; Horne, Anne M.; Reid, Ian R.
Abstract: Recent evidence suggests that Ca supplements increase the risk of cardiovascular events, but the mechanism(s) by which this occurs is uncertain. In a study primarily assessing the effects of various Ca supplements on blood Ca levels, we also investigated the effects of Ca supplements on blood pressure and their acute effects on blood coagulation. We randomised 100 post-menopausal women to 1 g/d of Ca or a placebo containing no Ca. Blood pressure was measured at baseline and every 2 h up to 8 h after their first dose and after 3 months of supplementation. Blood coagulation was measured by thromboelastography (TEG) in a subgroup of participants ( n 40) up to 8 h only. Blood pressure declined over 8 h in both the groups, consistent with its normal diurnal rhythm. The reduction in systolic blood pressure was smaller in the Ca group compared with the control group by >5 mmHg between 2 and 6 h ( P ≤0·02), and the reduction in diastolic blood pressure was smaller at 2 h (between-groups difference 4·5 mmHg, P =0·004). Blood coagulability, assessed by TEG, increased from baseline over 8 h in the calcium citrate and control groups. At 4 h, the increase in the coagulation index was greater in the calcium citrate group compared with the control group ( P =0·03), which appeared to be due to a greater reduction in the time to clot initiation. These data suggest that Ca supplements may acutely influence blood pressure and blood coagulation. Further investigation of this possibility is required.